The Use of English Among Sixth-Form Students in Malaysia - Sargunan, Rajeswary A. (Journal of Modern Languages, 2017)
The study attempts to reveal tendencies in the use of English by students in the sixth-form to be used as a spring board for more comprehensive and in-depth studies. The findings indicate that the students are interested in an English language course, and that they do have certain ideas about the objectives and components of such a course. The study also states that there is a need to explore more extensively the case for establishing an English language course in the sixth-form.